Analysis of Family Planning Services in Mohammad Hoesin Hospital Palembang on 2016 - Firmansyah Basir; Adik Wibowo; Amal C Sjaaf (HM Publisher, 2022)
Background. Family planning services in hospitals have been held since 1970 by the functional implementing unit led by obstetric and gynecologist specialists. Situational changes following decentralization in the 1990s caused policymakers and family planning practitioners' lack of attention to family planning services at province, district, and city levels. Data from 2002-2007 showed a decrease in family planning services from 6.2% to 4.9% in government hospitals and from 3.4% to 2.2% in private hospitals. The decrease in contraception use was affected by family planning users and providers. This study aims to analyze the factors contributing to family planning services in Mohammad Hoesin Hospital. Methods. This was a descriptive-analytic study with a cross-sectional design. The author used primary and secondary data with quantitative and qualitative approaches through the study of documents, observation, questionnaire, in-depth interview, and focused group discussion. Results. We identified various factors that play a role in the implementation of family planning services in almost all aspects, such as policy system, incomplete infrastructures; competence and the number of health workers; standard service procedure; sources and mechanism of the contraceptive tools; financial problems; recording and reporting system; quality control services; monitoring and evaluation; development services; also knowledge and behavior of the health workers. Conclusion. Family planning services need support and more serious attention from the directors to improve and overcome the problems and obstacles. In addition, the board of directors requires better coordination effort and cooperation on the internal level (between divisions or departments within the hospital) and with the relevant instance.